Suicide prevention via telemental health services: insights from a randomized control trial of crisis response plan and self-guided safety planning approaches - Monika Lohani; Justin C. Baker; Jamie S. Elsey; Sam Dutton; Samuel P. Findley; Scott A. Langenecker; Amy S. Do; Craig J. Bryan (BMC, 2024)
Abstract Background Although telemental health can make suicide prevention treatments more scalable and accessible, limited evidence demonstrates successful reductions in suicidality when interventions are administered through telehealth platforms. To address this limitation, the current work investigated the effects of two suicide prevention treatments - a clinician-guided Crisis Response Plan and a self-guided Safety Planning approach. Methods After completing the screening process, 82 participants with high suicide ideation and/or a lifetime history of suicidal behavior were randomly assigned across the two groups. Trained research clinicians administered the interventions using a videoconferencing platform. After the intervention delivery was complete, participants reported the therapeutic alliance they experienced with their clinician using an online survey. Participants also reported their overall suicidality 45 days after receiving the intervention. In addition, participants' perceived usefulness of the received intervention and actual use of the plan were recorded. Linear and logistic regression models predicted how suicidality, perceived utility, and actual use of their intervention protocols varied depending on the high (Crisis Response Plan) versus low (self-guided Safety Planning) level of clinician-led collaboration the two treatments entailed. Results Both Crisis Response Plan and self-guided Safety Planning were found to lower suicidality after receiving them via telehealth services. At the same time, those who received the Crisis Response Plan (the more collaborative form of therapy) reported experiencing a stronger therapeutic alliance with the clinician, utilizing the plan more often and perceiving it as more useful. These findings demonstrate the additional benefits of adopting a more collaborative approach because of its effectiveness and perceived utility, which has implications for suicide-related distress reduction in the short and long term. Conclusions Evidence from this randomized control trial suggests that Crisis Response Plan is a suitable candidate for delivering suicide prevention via telehealth platform because of its effectiveness in reducing suicidality and its collaborative approach to building a strong therapeutic alliance, perceived usefulness, and actual utility in everyday life. Trial registration This paper was part of a registered RCT: https://clinicaltrials.gov/study/NCT04888845 . Registration date: Date: 2021-04-22.